Analysis of elastic stress wave propagation through a complex composite structure. (11th November 2009) - Perez Jr., Francisco; Al-Haik, Marwan
A one-dimensional impact problem is employed for a layered system that comprises heterogeneous materials with different geometrical configurations. The system mimics transmitter for Multiple Integrated Laser Engagement Systems (MILES). The analytical model tracks the stress wave propagation through this layered structure as a result of the mechanical shock from blank rounds as they fired. The results clearly support the hypothesis that layered systems will suffer stress amplification with inherent acoustic impedance mismatch between layers. It is evident that the time dependent stress response in the rise portion is significantly affected by impedance mismatch and the number of layers.